Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Online di Marketplace Shopee - Alfin Muslikhun; Sutopo Sutopo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the factors that support the increase in online purchasing decisions in the Shopee marketplace. These factors consist of Online Customer Rating, Online Customer Review, Price, and Free Shipping. The population in this study were all Shopee user consumers with an unlimited number. While the sample used was all Shopee user consumers in the Gunungpati area and its surroundings which were calculated using the lemeshow formula and obtained 100 respondents. The results of hypothesis testing state that the four variables (Online Customer Rating, Online Customer Review, Price, and Free Shipping) have an influence on online purchasing decisions in the shopee marketplace both partially and simultaneously. Testing the coefficient of determination produces findings where the variables online customer rating, online customer review, price, free shipping are able to influence online purchasing decisions in the Shopee application by 89.5%. While the remaining 10.5% is influenced by other variables. Keywords : , , , ,